Making Sense of Change Management: A Complete Guide to the Models, Tools and Techniques of Organizational Change - Esther Cameron; Mike Green (USA Kogan Page, 2020)
The definitive, bestselling text in the field of change management, Making Sense of Change Management provides a thorough yet accessible overview for students and practitioners alike. Without relying on assumed knowledge, it comprehensively covers the theories and models of change management and connects them to practical approaches and techniques that organizations of all types and sizes can use to adapt to tough market conditions and succeed by changing their strategies, structures, mindsets, leadership behaviours and expectations of staff and managers. This completely revised and updated fifth edition of Making Sense of Change Management contains a new chapter on becoming a sustainable business, new material on the latest developments in technology-led change, further case studies and updated wider content with the latest thinking and developments. Supported by 'food for thought' and 'stop and think' features to aid critical thinking and understanding, as well as checklists, tips and summary boxes, it remains essential reading for anyone who is currently part of, or leading, a change initiative. New and updated online resources include international case study question packs for lecturers and lecture slides with reflective questions.
Keywords: Organizational change; Information technology; Management; Reengineering; Teams in the workplace; Managing People Through Change (HRM2076-N); (BIN3043-N) Project-Based Management